فاعلية الألعاب الإلكترونية التعليمية في تنمية بعض المهارات الصحية لدى أطفال التوحد: دراسة شبه تجريبية في محافظة اللاذقية - جبلاوي، رنيم خيرات (جامعة تشرين, 2021)
هدف البحث إلى التحقق من فاعلية الألعاب الإلكترونية التعليمية في تنمية بعض المهارات الصحية لدى عينة من أطفال التوحد في محافظة اللاذقية، تتراوح أعمارهم ما بين (5 -6) سنوات، وبلغت عينة البحث (12) طفل توحدي، تم تقسيمها إلى مجموعة تجريبية مؤلفة من (8) أطفال ومجموعة ضابطة مؤلفة من (8) أطفال. ولتحقيق هذا الهدف استخدمت الباحثة المنهج شبه التجريبي. وقد خضع أطفال المجموعة التجريبية لمجموعة من الألعاب الإلكترونية التعليمية بهدف تطوير المهارات الصحية لديهم. أظهرت النتائج وجود فروق دالة إحصائيا بين متوسط درجات أطفال المجموعة التجريبية ومتوسط درجات أطفال المجموعة الضابطة على اختبار المهارات الصحية بعد تطبيق الألعاب الإلكترونية التعليمية وذلك لصالح أطفال المجموعة التجريبية، ووجدت فروق ذات دلالة إحصائية بين متوسط درجات أطفال المجموعة التجريبية على اختبار المهارات الصحية في التطبيقين القبلي والبعدي، لصالح التطبيق البعدي. كما أظهرت نتائج الدراسة عدم وجود فروق دالة إحصائيا بين متوسط درجات أطفال المجموعة التجريبية في التطبيق البعدي ومتوسط درجاتهم في التطبيق المؤجل على اختبار المهارات الصحية. وفي ضوء النتائج أوصت الباحثة إجراء دراسات حول استخدام الألعاب الإلكترونية التعليمية في تنمية أنواع مختلفة من المفاهيم والمهارات لدى أطفال التوحد، وإجراء دراسات أخرى حول إعداد برامج لأطفال التوحد لتنمية مهارات مختلفة لديهم." The aim of the research is to verify the effectiveness of educational electronic games in developing some health skills among a sample of autistic children in Lattakia Governorate, their ages ranged between (5-6) years, and the research sample amounted to (12) autistic children, which were divided into an experimental group consisting of (8) children and a control group consisting of (8) children. To achieve this goal, the researcher used the quasi-experimental method. The children of the experimental group were subjected to a set of educational electronic games in order to develop their health skills. The results showed that there were statistically significant differences between the average scores of the children of the experimental group and the average scores of the children of the control group on the health skills test after the application of educational electronic games, in favor of the children of the experimental group, and there were statistically significant differences between the average scores of the children of the experimental group on the health skills test in the two tribal applications. and dimensional, in favor of dimensional application. The results of the study also showed that there were no statistically significant differences between the average scores of the experimental group children in the post application and their average scores in the delayed application on the health skills test. In light of the results, the researcher recommended conducting studies on the use of educational electronic games in developing different types of concepts and skills for autistic children, and conducting other studies on preparing programs for autistic children to develop different skills for them."
Keywords: الاضطرابات النفسية -- محافظة اللاذقية -- الانماط السلوكية